(untitled) (Eurasian Research Bulletin, 2021)
A contraction is a reduced version of a word, syllable, or word group generated by omitting internal letters and sounds from the spoken and written forms. Contractions are abbreviated words that combine two words into one with the use of an apostrophe. Contraction is something you hear in conversation and see in writing. Understanding how to use contractions correctly can assist you in mastering the English language. In linguistic analysis, contractions should not be confused with crasis, abbreviations, and initialisms (including acronyms), with which they share some semantic and phonetic functions, despite the fact that the term "abbreviation" is used interchangeably to refer to all three. In this article discusses about information and some grammar rules morpheme contraction in English.